2021
DOI: 10.3389/fmicb.2021.658668
|View full text |Cite
|
Sign up to set email alerts
|

Straw Mulching and Nitrogen Fertilization Affect Diazotroph Communities in Wheat Rhizosphere

Abstract: Diazotrophs that carry out the biological fixation of atmospheric dinitrogen (N2) replenish biologically available nitrogen (N) in soil and are influenced by the input of inorganic and organic substrates. To date, little is known about the effects of combined organic substrate addition and N fertilization on the diazotroph community composition and structure in purple soils. We investigated the effects of N fertilization and straw mulching on diazotroph communities by quantifying and sequencing the nifH gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…We efficiently differentiated RH and RP using a combination of approaches (Lucas et al, 2018). Upon analyzing microorganisms commonly associated with the wheat rhizosphere (Chen et al, 2019;Chen et al, 2021b;Elvia et al, 2021;Kavamura et al, 2021;Prudence et al, 2021), we observed that certain microorganisms were indeed highly abundant on the rhizoplane. It is likely that the greater abundance of Proteobacteria in the rhizoplane is due to increased root accessibility to nutrients (Ho et al, 2017;Ling et al, 2022).…”
Section: Microbial Responses In Different Microhabitatsmentioning
confidence: 99%
“…We efficiently differentiated RH and RP using a combination of approaches (Lucas et al, 2018). Upon analyzing microorganisms commonly associated with the wheat rhizosphere (Chen et al, 2019;Chen et al, 2021b;Elvia et al, 2021;Kavamura et al, 2021;Prudence et al, 2021), we observed that certain microorganisms were indeed highly abundant on the rhizoplane. It is likely that the greater abundance of Proteobacteria in the rhizoplane is due to increased root accessibility to nutrients (Ho et al, 2017;Ling et al, 2022).…”
Section: Microbial Responses In Different Microhabitatsmentioning
confidence: 99%
“…More than the amount of C, the quality of the soil organic matter seems to be more determinant to nitrogen fixation. Several authors report a positive correlation between soil C:N ratio and the diversity and activity of the diazotrophic community, so that higher C:N values could result in a competitive advantage for free-living diazotrophs (Mirza et al, 2014;Yang et al, 2019;Chen et al, 2021;Dai et al, 2021b).…”
Section: Non-symbiotic Nitrogen Fixationmentioning
confidence: 99%
“…Rev Bras Cienc Solo 2022;46:e0210098 Application of fertilizers, either chemical or organic, can favor nitrogen fixation by improving soil fertility, yet the response to nutrients availability is highly variable. Although nitrogen availability can have stimulatory effects on diazotrophic diversity (Poly et al, 2001), most of the recent studies evidence its negative effects on nitrogen fixation and diazotrophic abundance (Reardon et al, 2014;Zheng et al, 2019;Xiao et al, 2020;Chen et al, 2021;Dai et al, 2021b). Potassium can have negative (Hsu and Buckley, 2009), little or no effect (Tang et al, 2017), while phosphorus, in general, has stimulatory effects over nitrogen fixation (Tang et al, 2017;Zheng et al, 2019;Zheng et al, 2019).…”
Section: Non-symbiotic Nitrogen Fixationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, soil harbors the most diverse diazotrophic microbial communities, with Proteobacteria and Cyanobacteria as the most abundant members ( Gaby and Buckley, 2011 ). Many factors have been reported to affect the structure of diazotrophic community, such as temperature ( Feng et al, 2019 ) and precipitation ( Yeager et al, 2012 ), plant species richness ( Sheng et al, 2019 ), soil type and pH ( Zhang et al, 2018 ; Han et al, 2019 ), agricultural activities such as nitrogen fertilization ( Chen et al, 2021 ). In addition, some seasonal factors and growth cycle of the host plant ( Pereira et al, 2013 ) also regulated the diazotrophic communities that caused a clear seasonal succession of these microbes in some environments ( Zilius et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%